2018
DOI: 10.3390/mi9060278
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Au@C Core/Shell Nanoparticles by Laser Ablation in Solutions and Their Enhancements to a Gas Sensor

Abstract: A convenient and flexible route is presented to fabricate gold noble metal nanoparticles wrapped with a controllable ultrathin carbon layer (Au@C) in one step based on laser ablation of the noble metal targets in toluene-ethanol mixed solutions. The obtained metal nanoparticles were <20 nm in size after ablation, and the thickness of the wrapped ultrathin carbon layer was 2 nm in a typical reaction. The size of the inner noble metal nanoparticles could be controlled by adjusting the power of laser ablation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Compared with pure In 2 O 3 and Au-decorated In 2 O 3 , the Au@C-decorated In 2 O 3 film exhibits highly enhanced repeatability, good reversibility, and short response time to 1–5 ppm H 2 S at RT. 183 Wei et al 184 synthesized reduced graphene oxide (rGO)/SnO 2 /Au composite materials for the detection of methanol through a two-step method of hydrothermal reaction and in situ reduction. Compared with SnO 2 /rGO composite materials and pure SnO 2 samples, rGO/SnO 2 /Au composite materials exhibit better performance.…”
Section: Compounded Mos Functionalized With Au Npsmentioning
confidence: 99%
“…Compared with pure In 2 O 3 and Au-decorated In 2 O 3 , the Au@C-decorated In 2 O 3 film exhibits highly enhanced repeatability, good reversibility, and short response time to 1–5 ppm H 2 S at RT. 183 Wei et al 184 synthesized reduced graphene oxide (rGO)/SnO 2 /Au composite materials for the detection of methanol through a two-step method of hydrothermal reaction and in situ reduction. Compared with SnO 2 /rGO composite materials and pure SnO 2 samples, rGO/SnO 2 /Au composite materials exhibit better performance.…”
Section: Compounded Mos Functionalized With Au Npsmentioning
confidence: 99%
“…Notably, PLAL conducted in ethanol tends to yield larger NPs compared to DI water [36,49,50], while isopropyl alcohol has also been explored as a viable alternative [51]. Furthermore, previous PLAL investigations have explored the use of various organic solvents including toluene, tetrahydrofuran, and dimethylformamide to investigate their effects on the resulting NP size and morphology [52,53], Additionally, non-organic solvents like hydrogen peroxide have garnered attention [54]. It is important to emphasize that the specific choice of liquid medium exerts influence over colloidal density, UV-Vis absorbance, NP size distribution, and surface chemistry, given the differing interactions these liquids exhibit with the laser, the ablated material, and the synthesized NPs [28].…”
Section: Effect Of Mediummentioning
confidence: 99%
“…Laser ablation of a metal target in liquid media has been regarded as an efficient and green way for coating carbon layers onto particles of various metals. Duan et al reported on preparation of Au@C nanostructures via laser ablation of a gold target in mixed solutions of toluene and ethanol [ 15 ]. Amendola and coworkers fabricated magnetic Fe@C nanoparticles (NPs) by ablating bulk iron in various organic solvents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%